2011
DOI: 10.1227/neu.0b013e318208f1a0
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics of Carotid Arteries After Carotid Endarterectomy or Carotid Artery Stenting Based on Postoperative Patient-Specific Computed Tomography Angiography and Ultrasound Flow Data

Abstract: CFD of postoperative carotid arteries disclosed the differences in streamlines and WSS between CAS and patch CEA. CFD may allow us to obtain adequate rheological conditions conducive to achieving the best clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The authors showed a significantly lower strain after C-CEA, which is highly consistent with the WSS pattern of our C-CEA model. Hayase et al 25 compared postoperative hemodynamics after carotid artery stenting (CAS) with those after C-CEA with patch-angioplasty by use of CFD. Similar to the present study the authors showed an increased low and turbulent flow at the carotid bulb after C-CEA that may cause thrombogenesis and recurrent atheromatous plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed a significantly lower strain after C-CEA, which is highly consistent with the WSS pattern of our C-CEA model. Hayase et al 25 compared postoperative hemodynamics after carotid artery stenting (CAS) with those after C-CEA with patch-angioplasty by use of CFD. Similar to the present study the authors showed an increased low and turbulent flow at the carotid bulb after C-CEA that may cause thrombogenesis and recurrent atheromatous plaques.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 In recent years, computational fluid dynamics (CFD) have become an accepted technique for investigating flow alterations in anatomical correct models in carotid artery disease and assessment of rheological conditions comparing different operative techniques. [22][23][24][25][26][27][28][29] To the best of our knowledge, there has yet not been a CFD comparison between the postoperative morphologic and flow conditions in patients after C-CEA versus E-CEA.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation was performed by a Finite Volume solver, CFD-ACE (ESI-Group, France) by solving the transport equations -the Naviér-Stokes equations. Blood was treated as an incompressible and Newtonian fluid with a density of 1050kg/m 3 and a dynamic viscosity of 0.0035 Pa·s [14]. The average Reynolds number in these models varies between 649 to 793; thus, a laminar model of the flow was applied during the computation [15].…”
Section: Methodsmentioning
confidence: 99%
“…Several mechanical parameters such as wall shear stress (WSS) have been reported to present close relationships to the establishment of plaque and restenosis [4,8,9]. Some of the studies correlated preand post-operative hemodynamic parameters [10,11]; however, very few of them compared the operated vessel to the contralateral, untreated carotid artery [12]. In fact, the left and right carotid arteries together with the vertebral arteries function systematically to supply blood to the brain and other facial organs.…”
Section: Introductionmentioning
confidence: 99%
“…CFD is being increasingly employed to understand carotid stenosis and its biological properties according to geometric risks,33-36) or via virtual prototyping to recommend the best design for surgical reconstruction during a carotid endarterectomy,37) and conjunctional research magnetic resonance images 37-42). Furthermore, CFD is being used to better understand blood flow through an aneurysm in the abdominal artery, and the development and progression of aortic dissection 43-47).…”
Section: Applications In the Cardiovascular Systemmentioning
confidence: 99%